Synthesis and swelling behavior of temperature responsive kappa-carrageenan nanogels - Daniel-da-Silva, Ana L.
Crosslinked j-carrageenan hydrogel nanoparticles (nanogels) with an average size smaller than 100 nm were prepared using reverse microemulsions combined with thermally induced gelation. The size of the nanogels varied with biopolymer concentration at a constant water/surfactant concentration ratio. The nanogels were found to be thermo-sensitive in a temperature range acceptable for living cells (37– 45 C) undergoing reversible volume transitions in response to thermal stimuli. This opens the possibility to explore the application of these nanogels in smart therapeutics such as thermo-sensitive drug carriers. As such, the sustained release of methylene blue from the nanogels was evaluated in in vitro conditions as proof of concept experiments and the release rate was found to be controlled with temperature.